Laws and Acts on Access of Equal Property Rights in SAARC Region Countries - Acharya, Chiranjivi (Kaladarpan कलादर्पण, 2022)
Equal rights of parental property is defined that the sons and daughters have equal rights over the ancestral property. The property right is a national issue and it is also related to economy, which is one of the important factors for the development of the country. Main purpose of this article is to critically analyze the Laws and Acts on access of equal property rights in SAARC countries. Author has not collected and analyzed other information rather than Laws and Act related to Parental property rights of SAARC countries. Author has collected Secondary information from different sources and analyzed them critically with his own way. Furthermore, the collected information are based on SAARC regions (developing’ countries). Therefore, the Laws and Acts related to Parental property rights of developed and under’ developed countries cannot be generalized on the basis of these information. Author Has prepared this article maintaining the academic ethics and value. This article is based on qualitative information with cross sectional methods. The information are interpreted with inductive approach. However, information/ data are obtained by author from the different authentic and reliable sources and those are re-arranged and critically analyzed and make sensible as far as meaningful so readers could understand related issues. However, besides Maldives, other nation of SAARC regions have addressed the equal property rights through different ways, (e.g. customary laws, constitutions, women’s rights acts and laws and separate particular laws and Acts.